Balancing conservation planning and mitigation: perspectives from a case study of the Asiatic lions - Meena, V.; Macdonald, D. W. (Frontiers in Ecology and Evolution, 2023)
Diverse, often inter-disciplinary, approaches have been proposed to advance the conservation of lions (Panthera leo) and their natural habitats. The IUCN guidelines for the conservation of lions in Africa call for effective national policies at all scales, and legal frameworks with specific Action Plans preferably at a regional/population level, to achieve the goals of lion conservation while also planning for the equitable distribution of costs and benefits amongst local communities. However, general approaches must be tailored to specific circumstances, so here we provide an overview of the factors relevant to the particular case of Asiatic lions (p.l.leo). Taking stock of what has contributed to the remarkable recovery of these lions from the brink of extinction, we provide readers with background understanding of the steadily growing lion population in Gujarat, India. We focus on the management challenges that have arisen during the past two decades during which lions have increasingly moved, and dispersed, beyond the Gir Protected Area (Gir PA). We illustrate how the positive intersection between cultural predisposition, regulatory frameworks, and management interventions have contributed to this accomplishment. Despite the apparent history of success, the currently fruitful intersection of these factors are in fact dynamic and, to remain positive, need continuous review and adaptation. We highlight how mitigations that may strongly foster conservation when applied in moderation may be counter-productive in excess and also go on to evaluate the extent to which some of the lessons learnt can be generalised.